EFFORTS TO INCREASE PARENTS KNOWLEDGE ABOUT TODDLER’S DIARRHEA THROUGH ROLE PLAY AS A METHOD OF COMMUNITY EDUCATION IN JATISARI VILLAGE, PAKISAJI DISTRICT - Putri, Brillian Milenia Heryanti; Mahirasani, Dea Sabrina; Fadlan, Muhammad; Widhiastuti, Ni Made Susanti; Thalib, Sakinah Jamal; Rahmah, Shofi Nur; Dwicahyani, Safitri (Journal of Community Health and Preventive Medicine, 2023)
Diarrhea is a disease characterized by a change in the shape and consistency of the stool, which is looser or more liquid and the frequency of bowel movements is more than usual. This study aims to find out whether giving counseling about diarrhea can increase parents' knowledge about diarrhea and hand washing with soap. This study used a pre-experimental research design which was carried out in two stages, namely pre-intervention and intervention. At the pre-intervention stage, primary data collection was carried out through questionnaires to 35 respondents (parents who have toddlers in Jatisari Village, Pakisaji District) to determine problem priorities using the Nominal Group Technique (NGT) selected using the purposive sampling method. The data were then analyzed using the Wilcoxon Test. From the results of the pre-intervention questionnaire in Jatisari Village, Pakisaji District, it was found that 47.7% of parents who had toddlers did not know about diarrhea (including definition, causes, transmission, prevention and early treatment of diarrhea) and 7% of parents who had toddlers had not gotten used to washing hands with soap. From the results of the intervention carried out on 45 participants, an increase in the post-test scores of participants after the intervention was carried out by 91.1%, the post-test scores remained at 8.9%, and none of the participants had a decrease in post-test scores. The results of statistical tests using the Wilcoxon test found that the value of p = 0.000 (p <0.05), which means that there was a significant difference between the level of knowledge of the participants before and after the intervention.